Use of Biophysical Stimulation Therapy in Surgically Treated Acute Scaphoid Fractures - Carmine Scarlato; Macarena Vizcay; Nicoletta Denami; Andrea Ghezzi; Giorgio Eugenio Pajardi (Plastic and Reconstructive Surgery - Global Open, 2026)
Background: Scaphoid fractures remain challenging because of the bone’s limited vascularity, particularly at the proximal pole. Although surgical fixation represents the standard of care for displaced and high-risk fractures, pulsed electromagnetic field (PEMF) stimulation has been proposed as a noninvasive adjunctive therapy, with osteogenic, anti-inflammatory, bone-healing, and regenerative effects. Methods: This multicenter retrospective cohort study, conducted in accordance with the strengthening the reporting of observational studies in epidemiology (STROBE) guidelines, evaluated PEMF stimulation as an adjunctive treatment in acute surgically treated scaphoid fractures. Data from 26 male patients, aged 32 ± 13 years, treated between 2020 and 2023, with more than 1 year of follow-up, were analyzed. All patients underwent cannulated screw fixation and an early mobilization rehabilitation protocol. Radiographic consolidation, return to work, wrist pain (numeric pain rating scale), and disability in daily activities (Patient-Rated Wrist Evaluation) were evaluated and compared between the 2 groups. Results: Ten patients received postoperative PEMF stimulation and 16 served as controls. Radiographic consolidation occurred significantly earlier in the PEMF group ( P = 0.024). No significant differences were observed in return to work or Patient-Rated Wrist Evaluation scores. Pain at rest was significantly lower in the PEMF group ( P = 0.048). These results support the existing evidence on the biological impact of PEMF on bone healing and pain modulation; however, the small sample size and retrospective design limit causal inference. Conclusions: PEMF stimulation may represent a safe, noninvasive adjunct after surgical fixation of acute scaphoid fractures, potentially accelerating radiographic consolidation and reducing long-term wrist pain. Larger prospective studies are warranted.